A roadmap to advance dementia research in prevention, diagnosis, intervention, and care by 2025. (22nd February 2018) - Pickett, James; Bird, Cathy; Ballard, Clive; Banerjee, Sube; Brayne, Carol; Cowan, Katherine; Clare, Linda; Comas‐Herrera, Adelina; Corner, Lynne; Daley, Stephanie; Knapp, Martin; Lafortune, Louise; et al.
Abstract : Objective: National and global dementia plans have focused on the research ambition to develop a cure or disease‐modifying therapy by 2025, with the initial focus on investment in drug discovery approaches. We set out to develop complementary research ambitions in the areas of prevention, diagnosis, intervention, and care and strategies for achieving them. Methods: Alzheimer's Society facilitated a taskforce of leading UK clinicians and researchers in dementia, UK funders of dementia research, people with dementia, and carer representatives to develop, using iterative consensus methodology, goals and recommendations to advance dementia research. Results: The taskforce developed 5 goals and 30 recommendations. The goals focused on preventing future cases of dementia through risk reduction, maximising the benefit of a dementia diagnosis, improving quality of life, enabling the dementia workforce to improve practice, and optimising the quality and inclusivity of health and social care systems. Recommendations addressed gaps in knowledge and limitations in research methodology or infrastructure that would facilitate research in prioritised areas. A 10‐point action plan provides strategies for delivering the proposed research agenda. Conclusions: By creating complementary goals for research that mirror the need to find effective treatments, we provide a framework that enables a focus for new investment and initiatives. This will support a broader and more holistic approach to research on dementia, addressing prevention, surveillance of population changes in risk and expression of dementia, the diagnostic process, diagnosis itself, interventions, social support, and care for people with dementia and their families.